INsideVisible Cities: Transcending Substance - Vrabcheva, Zarya (Interiority, 2018)
The interior, as one of the most human and sensual forms of architecture, is an intimate connection with the built environment and a powerful tool in provoking and altering the human mind, stimulating its curiosity, desires and solutions by way of visible and ambient matter. I aspire to explore the sense of interiority as betweenness, a space of transition in which both the human and the architecture body transcend from one state to another through empathetic interaction. Empathy, besides the ability to feel and experience someone else’s emotions and mental state, also depicts our capacity to feel and experience situations, surroundings and non-living bodies. Interiority encounters three states of empathy in which our capacities of memory, imagination and illusion convey the invisible relationships we have with spaces and inanimate matter. Memory conveys the ability of both humans and space to encapsulate presence, activity and emotion through time. Imagination is our capacity to dream and inject a space with our own vision, shape and create new worlds. Illusion, on the other hand, forms a vigorous relationship with the human being through projecting its character and influence onto our minds. The interiority I seek to illustrate surpasses the rationalities, containment and materiality it is commonly related and rather stimulates curiosity in our being, revealing the qualities of a space as a living organism - growing, living, talking, affecting, absorbing, aging and eventually dying...